Anemia and Vitamin B12 and Folate Status in Women of Reproductive Age in Southern India (P10-101-19). (13th June 2019) - Finkelstein, Julia; Fothergill, Amy; Johnson, Christina; Guetterman, Heather; Bose, Beena; Jabbar, Shameem; Zhang, Mindy; Pfeiffer, Christine; Qi, Yan Ping; Rose, Charles; Bonam, Wesley; Crider, Krista
Abstract: Objectives: To conduct a biomarker survey to examine the anemia burden and vitamin B12 and folate status in women of reproductive age as part of an ongoing periconceptional surveillance program in Southern India. Methods: Participants were women of reproductive age (15–40 y) who were not pregnant or lactating and resided in households within the 50 km 2 catchment area of our community-based research site in Southern India. Venous blood samples were collected at enrollment ( n = 813), and whole blood samples were analyzed for hemoglobin using an automated Coulter counter. Plasma, serum, and red blood cells (RBC) were separated by centrifugation, processed, and stored <-80ºC until analysis. Total vitamin B12 was measured via chemiluminescence, and erythrocyte and serum folate concentrations were measured using the World Health Organization-recommended microbiological assay and chemiluminescence in a pilot sub-sample ( n = 75) at our laboratory at St. John's Research Institute in Bangalore, India. Anemia and severe anemia were defined as hemoglobin <12.0 g/dL and <8.0 g/dL, respectively. Vitamin B12 deficiency and insufficiency were defined as total vitamin B12 < 148.0 pmol/L and <221.0 pmol/L, respectively. Folate insufficiency was defined as RBC folate <748.0 nmol/L the recommended calibrator adjusted equivalent of the optimal neural tube defect prevention threshold. Results: A total of 39.1% of women in the overall study population were anemic and 2.7% had severe anemia. In the biomarker sub-sample, 18.9% of women were vitamin B12 deficient and 55.4% were vitamin B12 insufficient. Average RBC folate concentration was 486 (standard deviation: 227) nmol/L and the prevalence of RBC folate insufficiency, which is below the threshold for optimal neural tube defect prevention, was 83%. Conclusions: The substantial burden of anemia, as well as vitamin B12 and folate insufficiency in this pilot study population, suggest an opportunity for prevention of neural tube defects and anemia. Findings from the biomarker survey will inform the development of a randomized efficacy trial for the prevention of anemia and birth defects in Southern India. Funding Sources: Centers for Disease Control and Prevention ILSI North America Future Leader Grant AF was supported by the National Institutes of Health #5 T32 HD087137